Pengaruh Lingkungan Sekolah Berbasis Agama Terhadap Kualitas Pendidikan di MI Muhammadiyah - Slamet, Slamet; Harsono, Harsono; Wulandari, Murfiah Dewi (Jayapangus Press, 2025)
Education serves as a fundamental pillar in shaping high-quality human resources capable of facing global challenges. This study aims to analyze the influence of a religion-based school environment on the quality of education at MI Muhammadiyah Cekel. The research employs a quantitative approach with a correlational research design, involving students selected randomly as the sample. The research instrument consisted of a questionnaire that had been tested for validity and reliability. The findings indicate that a religion-based school environment, encompassing physical facilities, social interactions, and the application of religious and disciplinary values, has a significant impact on students' educational quality. Physical aspects such as comfortable classrooms and adequate library facilities, along with harmonious social relationships between students and teachers, contribute significantly to creating an effective learning atmosphere. The implementation of character values within the school environment also supports the development of more independent and high-achieving students. This study emphasizes the importance of optimizing school environment management through improving facilities, strengthening social interactions, and integrating character values to holistically support educational success at MI Muhammadiyah Cekel.